Ḥaḍānah conflict resolution through litigation: analysis of sharia court decisions in Aceh - Nispul Khoiri; Adelina Nasution (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This research aims to analyze the resolution of ḥaḍānah conflicts through litigation, specifically the decisions of the Sharia Court in Aceh regarding child custody (ḥaḍānah) to find legal certainty. This research uses a normative-empirical type of research by integrating normative law and empirical law. Normative legal analysis is carried out by examining library archives or secondary data. This research uses laws and judges' decisions in ḥaḍānah cases at the Aceh Syariah Courts. The instruments used in collecting data are observation, interviews, and documents or literature studies. To obtain research data on the number of ḥaḍānah cases that were filed separately at the Sharia Court, the article draws on existing decisions starting from 2016-2021. In this research, 5 (five) Sharia Courts were taken as research samples with 32 ḥaḍānah cases, particularly the Sharia Courts in Langsa, Kuala Simpang, Idi, Jantho, and Takengon. The research applies the theory of legal objectives according to Gustav Radbruch: legal certainty, justice, and expediency. The research shows that legal certainty through the decision of the Sharia Court has been realized. However, this has not provided justice for children because many defendants have not complied with court decisions, especially the surrender of child custody according to court decisions and payment of monthly child support according to what has been decided by the court. Hence, the benefits of the court decisions on the ḥaḍānah case are still not maximized. The solution is to formulate a law that is capable of providing a deterrent effect for defendants unwilling to fulfill court compliance.